2007
DOI: 10.1016/j.tcb.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Rings, bracelets, sleeves, and chevrons: new structures of kinetochore proteins

Abstract: Electron microscopy has recently revealed striking structural orderliness in kinetochore proteins and protein complexes that associate with microtubules. In addition to their astonishing appearance and intrinsic beauty, the structures are functionally informative. The Dam1 and Ndc80 complexes bind to the microtubule lattice as rings and chevrons, respectively. These structures give insight into how the kinetochore couples to dynamic microtubules, a process critical to the accurate segregation of chromosomes. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Therefore, for this coupling to be biologically successful, there must be some additional mechanism that ensures its attachment. For example, the stability of Dam1 ring attachment might be augmented by other kinetochore proteins and/or proteins that bind MT plus ends (40). Such interactions are possible, but their effects on ring motility are speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, for this coupling to be biologically successful, there must be some additional mechanism that ensures its attachment. For example, the stability of Dam1 ring attachment might be augmented by other kinetochore proteins and/or proteins that bind MT plus ends (40). Such interactions are possible, but their effects on ring motility are speculative.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the process of cold shock and kinetochore retrieval, we found that Dam1 and Klp2 can decorate the INMs either as single or multiple dots and always colocalize with the kinetochore during its retrieval. Because these dots could either be the plus ends of microtubules within a bundle or other structures along the microtubule (Davis and Wordeman, 2007), we cannot at this time discriminate between these different hypotheses (i.e., kinetochore retrieval by surfing along the INM and kinetochore retrieval by selective microtubule shrinkage within the INM).…”
Section: Discussionmentioning
confidence: 99%
“…Two independent screens (Newman et al 2000;Wong et al 2007) have found Zip1p to be physically interacting with two different components, Nuf2p and Spc24p, of the outer kinetochore complex Ndc80. The Ndc80 complex plays a vital role in chromosome segregation and mediates interaction between the kinetochores and the spindle microtubules during chromosome movement (reviewed by Kotwaliwale and Biggins 2006;Ciferri et al 2007;Davis and Wordeman 2007;Westermann et al 2007;Tanaka and Desai 2008). Zip1p's multiple interaction with this kinetochore complex raised the possibility that two molecules of Zip1p could connect two sister kinetochores in a manner analogous to the way they connect two lateral elements in the SC (fi gure 3B), and that this Zip1p-mediated interaction between sister kinetochores might promote mono-orientation in meiosis-I.…”
Section: Role Of the Synaptonemal Complex In Monopolar Orientationmentioning
confidence: 99%